Daylight modelling of Portland building of Portsmouth University - Barbhuiya, S.; Barbhuiya, Salim; Nikraz, Hamid (Global Science & Technology Forum, 2013)
In this paper an attempt has been made to provide recommendations to improve the summer and winter performance of the daylight strategy of Portland Building of Portsmouth University. Daylight modelling was undertaken for five selected spaces viz. third floor office room, third floor south facing studio, north facing studio in the third floor, ground floor office room and atrium of the building as a means of providing advice on likely daylight performance, possible options for improving this performance and suggestions for artificial lighting control strategy based on daylight levels. The spaces have been simulated as base case and then various interventions were made to improve the daylight performance. Based on the modelling it can be concluded that the third floor office room although adequately daylit poses a problem of glare which can be addressed by adopting an external shading element over the window. The performance of third floor south facing studio can be enhanced by introducing roof lights. The north facing studio in the third floor has the problems with low lighting levels due to its orientation. This can be resolved by the introduction of roof lights south side of the ceiling leading to improved performance and uniformity of daylight. The ground floor office room can be improved by adding a light shelf and refractive glazing. The atrium can be improved by using high reflectance surface materials for floor and ceiling in order to have an acceptable apparent lightness.